Pengaruh Jarak Tingkatan Berbeda Terhadap Laju Pertumbuhan Rumput Laut Kappaphycus alvarezii Dengan Metode Lepas Dasar Bertingkat - Muhammad Yusuf; Henky Irawan; Rika Wulandari (Program Studi Budidaya Perairan Universitas Maritim Raja Ali Haji, 2021)
This study aims to determine the best stratification distance in the cultivation of Kappaphycus alvarezii seaweed with stratified off-bottom method. This research waswas conducted for 52 days, starting from May to June 2021, in Berakit Village, Riau Islands. The method used waswas Completely Randomized Design (CRD) with 3 treatments and 3 replications, where Treatment A (Level Distance 25 cm), Treatment B (Level Distance 35 cm) and Treatment C (Level Distance 45 cm). The results of the study after the statistical test of variance ANOVA, the effect of different levels of distance ons the growth rate of seaweed Kappaphycus alvarezii stratified off-base method did not give a significant effect ons the growth rate of seaweed (p> 0.05). Where the results obtained in the Absolute Weight Growth parameter (g) Level 1: A (221.56±13.83), B (243.10±19.98), C (290.77±24.71) and PBM ( g) Level 2: A (259.04±42.08), B (269.77±41.87) and C (309.76±12.68). Specific Growth Rate (g) Tier 1: A (5.28±0.33), B (5.58±0.48), C (6.92±0.59) and LPS (g) Tier 2: A (6.82±1.00), B (6.20±0.94) and C (7.38±0.30). Survival rates in treatments A, B, and C Levels 1 and 2 obtained the same or identical results (100±0.00).